Successful closure of ileostomy in a patient with intestinal Behçet's disease after therapy with adalimumab: A case report. Issue 9 (March 2019) - Yan, Zhe; Cui, Bei-Bei; Yu, Yong-Yang; Yin, Geng; Cen, Xiao-Min; Xie, Qi-Bing
Abstract: Rationale: Behçet's disease (BD) is a chronic immune-mediated inflammatory disorder involving multiple organ systems. In BD, intestinal ulcers can present as a refractory lesion capable of perforation, which makes the choice of treatment difficult. Patient Concerns: A 34-year-old male who was diagnosed with intestinal BD and suffered with an ileocecal perforation. He underwent surgery for an ileostomy and was given corticosteroids as treatment. However, the ulcerative lesion remained resistant to the therapy that was provided which delayed the closure operation. Diagnosis: Intestinal BD with severe post-operative complication. Interventions: A course of adalimumab (ADa) therapy was started. Subsequently surgery was performed. And ADa and thalidomide were used as a maintenance therapy. Outcomes: In this case, a course of ADa therapy was given which healed the intestinal ulcers and allowed us to successfully perform the closure operation. Lessons: This case indicates that ADa may be an effective treatment option in future cases, minimizing complications and allowing the closure operation to be performed successfully.